Effectiveness of Dose and Application Interval of Ocimum sanctum Essential Oil as Bactrocera spp. Attractant on Siamese Orange Plants - Amri, Lutfir Rahman; Arneti, Arneti; Reflinaldon, Reflinaldon; Syahrawati, My (Jurnal Proteksi Tanaman, 2024)
Fruit flies (Bactrocera spp.) are the most detrimental pests on siamese orange fruit (Citrus nobilis Linnaeus). One technique to control fruit flies that are safe for the environment and do not cause residues on plants is the use of attractants. The research aimed to study the effect of dose and application interval of basil essential oil for fruit fly control on Siamese orange plants. This research was conducted in citrus plantations of Gunung Omeh District, Lima Puluh Kota Regency, West Sumatra, Indonesia, and Insect Bioecology Laboratory, Faculty of Agriculture, Universitas Andalas. The study used a separate plot design consisting of doses of basil essential oil as the main plot and application intervals as subplots. The observed variables were species and the population of fruit flies. The results of observations found Three species of fruit flies, namely Bactrocera dorsalis, Bactrocera carambolae, and Bactrocera umbrosa, were successfully trapped during the observation with the highest number of catches of 278.33 individuals/trap, 15.33 individuals/trap, and 2.67 individuals/trap, respectively. Basil essential oil with a dose of 1.5 ml and an application interval of 3 days proved to be the most effective combination in trapping fruit flies compared to other doses and intervals. These results indicate that basil essential oil can be a potential alternative attractant in managing fruit fly populations on Siamese orange plants